Criteria base of the Hartmann–Sprenger pipe workflow - V. V. Makarov; V. I. Kuznetsov; I. O. Kuznetsova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The issue of creating a criteria base for the Hartmann–Sprenger pipe workflow based on a closed mathematical model is considered. On the basis of a closed mathematical model, the main parameters affecting the increase in the total temperature of the gas at the end of the dead-end cavity above the deceleration temperature of the incoming flow are recorded. Parameters with the same dimension are combined into one group so that only one dimensionless complex is obtained for all these quantities. Finding dimensionless complexes based on the modeling theory allowed us to determine the criteria base of the Hartmann–Sprenger pipe workflow.